Evaluation of electrocardiographic predictors of brugada type response during flecainide challenge. (14th October 2021) - Shen, X; Zhang, A.A; Sia, C.H; Tan, B.Y; Lim, P.C.Y; Chua, K.C.M; Ho, K.L; Lim, E.T.S; Ching, C.K; Chong, D.T.T
Abstract: Background/Introduction: Brugada syndrome (BrS) is a hereditary channelopathy with an increased risk of sudden cardiac death. Most BrS patients manifest non type 1 Brugada pattern electrocardiography (ECG). Sodium channel blockade is a well-established diagnostic tool for Brugada syndrome. However, intravenous sodium channel blockade is not readily available in all parts of the world. In addition, severe ventricular arrhythmias during drug challenge have an estimated prevalence of 1%. Determining the predictors of a positive test would improve our understanding and facilitate appropriate use of these tests. Purpose: We aimed to identify ECG predictors of Brugada type response during flecainide challenge and provide an independent assessment of current published ECG criteria predictive of a positive flecainide challenge. Methods: We analysed the clinical and electrocardiographic data of 526 consecutive individuals referred from a national pre-participation exercise screening program who underwent flecainide challenge for an ECG suspicious of Brugada pattern. ECG recordings included both conventional and high precordial leads (1 and 2 space up ECGs in V1 and V2 – 1V1, 1V2, 2V1, 2V2). Twelve-lead ECGs were evaluated for the width of the β angle, β score, baseline J wave elevation, width of QRS, absence of isoelectric segment in lead II, ST/ QT ratio, presence of S wave in Leads II, III and V5 as well as the presence of R wave in aVR. Results: Flecainide challenge was positive in 121 (23%) of the 526 cases. Baseline QRS duration was greater in the conventional lead placement [V1 (102.4±20.0 ms vs 97.6±14.0 ms, p=0.003), V2 (111.1±33.5 ms vs 100.9±13.1 ms, p=0.001)] as well as 1 space up [1V1 (108.9±21.0 ms vs 100.6±18.2 ms, p<0.001), 1V2 (117.4±26.6 ms vs 103.2±18.3, p<0.001)] and 2 space up [2V1 (113.6±23.4 ms vs 102.5±19.3 ms, p<0.001), 2V2 (121.6±26.1 ms vs 106.8±19.1 ms, p<0.001)] in cases with a subsequent positive response. A QRS duration of ≥120ms in V2 yielded a sensitivity of 16.5%, specificity of 93.8%, positive predictive value of 44.4% and negative predictive value of 79% for a positive flecainide challenge. Other predictors of positivity included that of a shorter ST duration in lead II (107.0±19.9 ms vs 118.1±24.4, p<0.001) and a shorter ST/ QT ratio (0.30±0.09 vs 0.32±0.07, p=0.006). Conclusion: In this population, a wider QRS duration, shortened ST segment in lead II and ST/QT ratio were predictors of a positive response to flecainide challenge when BrS was suspected on a baseline ECG. Prior published ECG parameters such as β angle, β score, baseline J wave elevation, presence of S wave in Leads II, III and V5 as well as the presence of R wave in aVR did not perform as well in predicting for a positive response to flecainide challenge in our population. Funding Acknowledgement: Type of funding sources: None.